Cannabis in the capital: exploring the spatial association between medical marijuana dispensaries and crime - Zakrzewski, Willliam J.Jr. (Journal of crime and justice, 2020)
The legalization of medical marijuana remains a controversial policy. An important dimension of marijuana legalization is the siting of dispensaries and their influence on a surrounding community. Specifically, dispensaries, if they engender criminogenic opportunities via changes in routine activities, have the potential to increase crimes in the areas surrounding medicinal marijuana dispensaries (MMDs). Using a quasi-experimental design, we examine the relationship between MMDs and crime using micro-spatial units in a novel location. Street level geocoded crime data for violent and nonviolent crime patterns before and after the opening of MMD’s in Washington, D.C. Crime is analyzed with 100 m buffers around each dispensary and control location drawn from propensity score matching. Differences between crime rates pre- and postoperation are compared. With the exception of one location, crime decreased or remained constant in geographical areas following the opening of a dispensary. MMDs do not appear to have an immediate criminogenic effect. Implications for future research regarding potential confounding factors and data limitations are discussed.